PsycEXTRA Dataset 2006
DOI: 10.1037/e527352012-769
|View full text |Cite
|
Sign up to set email alerts
|

The effect of type and timing of feedback on learning from multiple-choice tests

Abstract: Two experiments investigated how the type and timing of feedback influence learning from a multiplechoice test. First, participants read 12 prose passages, which covered various general knowledge topics (e.g., The Sun) and ranged between 280 and 300 words in length. Next, they took an initial six-alternative, multiple-choice test on information contained in the passages. Feedback was given immediately for some of the multiple-choice items or after delay for other items. Participants were either shown the corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 16 publications
0
22
0
1
Order By: Relevance
“…Overall, the results obtained in these two experiments confirm several points uncovered in previous research. Many studies have found that taking a prior test improves performance on a future test (e.g., Carpenter & DeLosh, 2006;Roediger & Karpicke, 2006b;Wheeler & Roediger, 1992; for a review, see Roediger & Karpicke, 2006a) and that providing feedback after an initial test enhances subsequent test performance (e.g., Butler, Karpicke, & Roediger, 2007;Butler & Roediger, 2008;McDaniel & Fisher, 1991;Pashler et al, 2005). In addition, several studies have found that providing feedback after incorrect responses is critical to correcting errors (e.g., Lhyle & Kulhavy, 1987;see Bangert-Drowns et al, 1991), especially those errors committed with high confidence (Butterfield & Metcalfe, 2001.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the results obtained in these two experiments confirm several points uncovered in previous research. Many studies have found that taking a prior test improves performance on a future test (e.g., Carpenter & DeLosh, 2006;Roediger & Karpicke, 2006b;Wheeler & Roediger, 1992; for a review, see Roediger & Karpicke, 2006a) and that providing feedback after an initial test enhances subsequent test performance (e.g., Butler, Karpicke, & Roediger, 2007;Butler & Roediger, 2008;McDaniel & Fisher, 1991;Pashler et al, 2005). In addition, several studies have found that providing feedback after incorrect responses is critical to correcting errors (e.g., Lhyle & Kulhavy, 1987;see Bangert-Drowns et al, 1991), especially those errors committed with high confidence (Butterfield & Metcalfe, 2001.…”
Section: Discussionmentioning
confidence: 99%
“…16,21,22 An evaluation of first-year medical students validated this finding in a professional health program. 23 There may also be additional benefit to using multiplechoice self-testing questions when multiple-choice questions are the primary evaluation tool used by the course.…”
Section: Discussionmentioning
confidence: 99%
“…6 Finalement, en raison de l'anonymisation et du concept de l'étude, la rétroaction aux sujets de l'étude des résultats du test à choix de réponses a été quelque peu limitée; pourtant, la rétroaction améliore l'effet de test, et nous avons des données probantes qu'une rétroaction retardée est plus efficace qu'une rétroaction immédiate pour promouvoir la rétention d'informations à long terme. 7 La durée des sessions d'apprentissage est un autre facteur bien connu qui influence la rétention d'informations factuelles. Lorsqu'il s'agit de multiples sessions brèves, on parlera d'apprentissage distribué, alors que pour une longue session, le terme employé est apprentissage massé.…”
Section: Enseigner Launclassified
“…6 Finally, due to anonymization and the study design, feedback of the MCQ results to subjects was precluded to some extent; however, feedback enhances the testing effect, and there is some evidence that delayed feedback is more effective than immediate feedback on promoting long-term retention of information. 7 Another well established influence on the retention of factual information is the duration of the learning sessions. Multiple short sessions are referred to as distributed learning, whereas one lengthy session is referred to as massed learning.…”
mentioning
confidence: 99%